Interaction of 2'-deoxyguanosine with cis-2-butene-1,4-dial: Computational approach to analysis of multistep chemical reactions - Sviatenko, L.K.; Gorb, L.G.; Hovorun, D.M.; Leszczynski, J. (Вiopolymers and Cell, 2014)
cis-2-Butene-1,4-dial represents a microsomal metabolite of furan, an industrially important chemical found in cigarette smoke, air pollution, and also in canned or jarred food. It is expected to be a human carcinogen. Aim. Investigation an effect of cis-2-butene-1,4-dial on the 2'-deoxyguanine which is a model of DNA site. Methods. Optimization of reaction species molecular structures, spectral parameters and Gibbs free energy calculations were performed using Gaussian09 program. Systems of differential equations for kinetics generation were solved using Mathcad15 program. Results. The predicted mechanism of the reaction of cis-2-butene-1,4-dial with 2'-deoxyguanine consists of four-step process formation of four diastereomeric primary adducts and further base-mediated five-step transformation of the primary adducts to the secondary one. The reaction kinetics, which allows defining theconcentration change of any reaction species was calculated. Conclusions. Under physiological conditions the interaction between cis-2-butene-1,4-dial and 2'-deoxyguanine leads to the formation of a stable adduct which could be responsible for the furan genotoxicity.